University tuition fees and high school students' educational intentions - Michael Bahrs; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper studies whether higher education tuition fees influence the intention to acquire a university degree among high school students and, if so, whether the effect on individuals from low-income households is particularly strong. We analyze the introduction and subsequent elimination of university tuition fees in Germany across states and over time in a difference-in-differences setting. Using data from the Youth Questionnaire of the German Socio-Economic Panel (SOEP), we find a large negative effect of tuition fees on the intention of 17-years-olds to acquire a higher educational degree, with a decrease of around eight percentage points (ten percent). Individuals from low-income households mainly drive the results. This study documents that the introduction of relatively low university tuition fees of 1,000 euros per academic year can considerably lower young people's educational intentions and choices.
Keywords: I22; I23; I24; 330; tuition fees; educational inequality; difference-in-differences